An augmented outdoor workout system for jogging and calisthenics support - Armandi, Vincenzo; Stacchio, Lorenzo; Cascarano, Pasquale; Hajahmadi, Shirin; Donatiello, Lorenzo; Marfia, Gustavo (Frontiers in Virtual Reality, 2025)
In this paper we introduce M-AGEW (Magic AuGmentEd Workout), an Augmented Reality (AR) application that assists users during outdoor, high-dynamic workouts such as jogging and calisthenics. It is a client-server-based system with a proprietary data structure (WKAN) that dynamically defines sequences of workouts as finite state machines. M-AGEW adapts workout intensity dynamically based on real-time sensor data and overlays contextual AR feedback and guidance, including biometric readings and a virtual coaching avatar. The technology was created through a user-centric design process, supported by an initial user study and industrial partnership. We validate M-AGEW through a technology acceptance evaluation with professional athletes, reporting promising results in usability, enjoyment, and perceived usefulness. Our findings suggest that AR headsets can effectively enhance and supplement outdoor physical activity, offering a motivating alternative to standard fitness monitoring.